Afghanistan in the Heart of Asia: Geopolitical Fragmentation, Climate-Induced Fragility, and the Future of Eurasian Connectivity - Sail, Ezat Ullah; Miakhil, Jan Mohammad (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
Central Asia is currently undergoing a profound transformation in regional cooperation, shifting from a passive geopolitical space to an active agent asserting itself through new connectivity initiatives and multisector diplomacy. However, the realization of a cohesive regional order is inextricably linked to Afghanistan's stability and integration. Despite its geographic centrality as the